Kajian Nilai-nilai Toleransi dan Gotong Royong Pada Permainan Tradisional di Kabupaten Sumenep - Salamet Wahedi; Mufti Syaifuddin; Hodairiyah (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2024)
The existence of traditional games has indirectly shown the public the cultural results of a community group. Traditional games are a reflection of people's behavior in building their civilization. Remembering that traditional games have a basis in local culture or local wisdom that exists in the community itself. Traditional games, also known as folk games, are a recreational activity that not only aims to entertain oneself, but also as a tool to maintain social relationships and comfort in society. It is correct to say that play is a necessity for children, so that children gain value and progress in the development of daily life. Through traditional games, the values ​​of tolerance are introduced and instilled in individuals. Instilling the values ​​of tolerance through traditional games will be fun and not boring. The terminology "gotong royong" comes from Javanese, namely the word gotong which means to shoulder and the word royong which means to be together. The combination of the words gotong royong, if interpreted entirely, means working together to complete a particular activity involving joint activities. The method used in the research is a qualitative method. Qualitative methods are research procedures that produce descriptive data, speech or writing and observable behavior from people (the subjects themselves).